Introductory Thoughts About the Universal Protection of Human Rights - Kovács, Péter (The Universal Protection of Human Rights, 2026)
Abstract: The introductory article gives a short overview of the historical evolution of the international acceptance of human rights. Signing first treaties about freedom of religion, states progressively made commitments on minority protection, citizenship issues, humanitarian law, labour law and following the trauma of World War Two, they also accepted that each human possesses inalienable rights. From this perspective, one of the greatest achievements of the 20th century international law-making is the recognition of human rights as well as ensuring their appropriate procedural guarantees. The article highlights the main fruits of the universal standard setting, the different treaty based and charter-based monitoring bodies and their activities.Keywords: Human rights, United Nations, conventions, monitoring, national implementation